The importance of quantifying fitness-determining traits throughout life to assess the application of reproductive technologies for amphibian species recovery - Silla, Aimee J.; Byrne, Phillip G. (Frontiers in Conservation Science, 2024)
The application of reproductive technologies to amphibian conservation breeding programs is gaining momentum and the field is poised to contribute significantly toward amphibian species recovery. We briefly discuss the opportunities for reproductive technologies to enhance conservation breeding outcomes, including their potential to enhance the genetic management, and in turn, the fitness of threatened species. Despite this potential, an important consideration that is not yet well understood is the degree to which specific reproductive technologies might influence (either enhance, or in some instances potentially decrease) individual fitness and lead to shifts in population viability. The development of a standardised approach to monitoring offspring throughout life-stages to detect changes to morphology, behaviour, physiology, survivorship, and developmental trajectories is essential. The primary focus of this review is to provide a ‘best-practise’ framework for quantifying key fitness determining traits expected to contribute to the fitness of individuals and long-term viability of populations, which will ultimately allow us to progress the field of amphibian reproductive technologies and assess the impact of protocol refinement.